La bataille contre l’impunité de la torture pendant la Guerre d’indépendance algérienne : que dit l’histoire ? - Sylvie Thénault (Criminocorpus)
The development of international law has made the fight against impunity one of the pillars of the non-recurrence of crimes. The torture practised during the Algerian war of independence provides a particularly exemplary case study in this respect. While torture remained illegal, it went unpunished, not least because of the post-1962 amnesty. This impunity was denounced and fought against during the war itself, in France. History shows, therefore, that the issue of punishment for torture and reparations for the victims is not anachronistic; it was raised during the war itself. Looking back at the history of this impunity also highlights the crucial issue of amnesty. Finally, knowing what has been done and what has been attempted provides a useful overview. If there are dead-ends, it also points to potential avenues for the future.